Perilaku Ibu Hamil di Era New Normal - Siti Rochimatul Lailiyah; Maya Wiwit Fiastutik; Dwi Wahyuning Tyas; Lelly Aprilia Vidayati (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2022)
During the Covid-19 pandemic, there were some fundamental changes in the behavior of pregnant women in carrying out antenatal visits. The purpose of this study was to describe the behavior of pregnant women during the Covid pandemic. The research design used is descriptive quantitative. The variables in this study were the application of health protocols, nutrition fulfillment, TT immunization and pregnancy visits. The population in this study based on estimates of midwives was 21 people with a sample of 20 people. The sampling method is using Non Probability Sampling in Total Sampling, data collection is using questionnaires and observation sheets. The results showed that most of the pregnant women implemented the health protocol, namely 15 pregnant women (75%), all of the pregnant women had their nutrition fulfilled, namely as many as 20 pregnant women (100%), almost all of the TT immunization status of pregnant women was incomplete, namely as many as 17 pregnant women (85%), most of them are not routine in conducting ANC visits in the new normal era, namely as many as 13 pregnant women (65%). It is expected that pregnant women will continue to conduct classes for pregnant women during the pandemic by implementing health protocols, conducting integrated ANC and providing KIE through cross-program and cross-sectoral implementation of health protocols during the pandemic